A Mini Review of Research Progress of Nuclear Physics and Thermal Hydraulic Characteristics of Lead-Bismuth Research Reactor in China - Wang, Bo; Chen, Bowen; Wen, Jiming; Tian, Ruifeng (Frontiers in Energy Research, 2020)
The lead-bismuth research reactor is one of the most important generation-IV reactors. Currently, Chinese scholars are very enthusiastic about studying lead-bismuth research reactors. Based on the research results in the papers that have been published, research progress on lead-bismuth research reactors in some Chinese research institutes such as the Chinese Academy of Sciences, Shanghai Jiaotong University, the University of Science and Technology of China, and the Insitute of Nuclear and New Energy Technology of Tsinghua University have been conducted. Firstly, Chinese academics attach great importance to the safety analysis of lead-bismuth research reactors in the event of an accident. Besides, CLEAR-I has negative reactivity coefficient feedback, which reflects its safety. The determination of the flow state of the liquid metal will be a prospect for future research. Besides, SMPBN (Small Modular Pb-Bi Cooled Reactor with Nitride Nuclear Fuel) is easy to control during its lifetime and has inherent safety features. China lags behind its international counterparts in MA transmutation. This is also an important prospect in future research. This review is expected to provide a reference for the research of lead-bismuth research reactor.